Outcomes of cryoablation for small renal masses: a single-institution study - Waqar, Muhammad; Faraz, Ahmad; Velurajah, Rajalaxmi; Karri, Rama S.; Khan, Azhar (International Surgery Journal, 2022)
Background: The current study reports the clinical outcomes of the efficacy of computerized tomography (CT) guided cryoablation (CA) in the treatment of patients with small renal masses. Methods: This retrospective single institution study analyses the clinical outcomes of 36 renal tumours that were managed with cryoablation. Patient age, sex, tumour size, complications and recurrences were recorded. These patients were followed up at 3,6- and 12-months interval, they underwent biopsy and abdominal contrast enhanced ultrasound (CEUS) depending upon indications. Results: 36 patients (63.9% male, 19.4% female) each with a single small renal mass had CA with a follow-up at 3, 6 and 12 months. The mean tumour size was 606.9±31.8 mm2. Eleven complications occurred in 36 patients, for an overall complication rate of 30.6%. One (2.7%) patient had enhancement at the surgical bed on initial imaging and were considered incomplete ablations. None of the patients showed signs of distant metastases at the 3, 6 and 12-month follow-ups. Conclusions: Cryoablation of renal masses results in acceptable oncologic efficacy with an acceptable number of complications. Therefore, it remains a viable treatment for renal masses.